Debt policy and economic growth in a small open economy model with productive government spending - Koichi Futagami; Takeo Hori; Ryoji Ohdoi (Asian Development Bank Institute (ADBI), 2010)
In this paper, we examine the effects of introducing constraints on government borrowing using a continuous-time overlapping generations model of a small open economy. We consider government placing constraints on the amount of government bonds outstanding by establishing an upper limit, or target level, for the ratio of government bonds to gross domestic product. We first show that there exist multiple steady states in the model small open economy. One is a steady state with high growth, the other a steady state with low growth. We next examine how changes in the target level for bonds affect economic growth rates at the steady states. If the economy has a positive amount of asset holdings, we obtain the following results. When the government runs budget surpluses, an increase in the target level for government bonds reduces the growth rate of the low-growth economy, but raises the growth rate of the high-growth economy. However, when the government runs budget deficits, an increase in the target level for government bonds raises the growth rate of the low-growth economy, but reduces the growth rate of the high-growth economy. If the economy has a negative amount of asset holdings, the results are ambiguous.
Keywords: 330; Haushaltskonsolidierung; Verschuldungsrestriktion; Steady-State-Wachstum; Overlapping Generations; Kleines-offenes-Land; Theorie